M15 Nebulised bronchodilators pre-bronchoscopy in patients with obstructive lung disease: does it help?. (14th November 2013) - Gupta, V; Jackson, N; Rossall, M; Kolsum, U; Budd, R; Southworth, T; Singh, D
Abstract : Background: Patients with Chronic obstructive pulmonary disease (COPD) and asthma may be at higher risk of complications during bronchoscopy. Previous guidelines have recommended that all patients with asthma receive nebulised bronchodilators pre procedure. At our research centre, we changed our practice in January 2012; since this date we administer nebulised salbutamol to all patients with COPD and asthma pre-bronchoscopy. Aims: We examined research bronchoscopy records from asthma and COPD patients with and without nebulised bronchodilators to determine tolerance of procedure, complications and adverse events, sedation used and success of obtaining samples. We have also examined the overall safety of research bronchoscopies. Methods: A retrospective analysis of case report forms of 140 (65 asthma and 75 COPD) patients who underwent research bronchoscopy at our centre since November 2010. Results: See Table 1 for details. Baseline characteristics were the same among COPD and asthma patients who did and did not receive bronchodilators. There was no significant change in procedure tolerance, sedation used, complications or adverse events and samples obtained in patients who received pre-procedure bronchodilators. Mean volume of saline inserted for BAL during bronchoscopy was 414.3 ± 140.5 ml for asthmatics and 392.1 ± 123.5 ml for COPD patients. Overall, serious complications were rare: 2 patients bled during the procedure requiring cold saline and adrenaline, 1 was observed for a few hours due to low saturations, 1 was admitted overnight for hypotension and 1 was admitted with pleuritic chest pain. 41 patients were symptom free at 24 hours and 85 were symptom free at 7 days. The most common mild symptom reported at 24 hours was sore throat, being reported by 50 patients; at 7 days 21 patients reported cough. Conclusion: Nebulised bronchodilators pre-bronchoscopy in patients with asthma or COPD appears to have little impact. Overall, research bronchoscopy with significant BAL in these patients appears relatively safe. * The first 2 authors contributed equally to this work.